The role of Sulh in cross-cultural disputes resolution and referrals to ICJ and ICA: An evaluation - Kadouf, Hunud Abia; Sambo, A.O. (INSI Publications, 2012)
The world has become a global village. This makes social interactions inevitable where people of different cultures and religions meet. Disputes in the course of such interactions become unavoidable. This is mainly as a result of cultural conflicts. Despites this, many nations do not put in place effective measures for resolving conflicts across cultures. Rather, some countries put in place legal measures to undermine and suppress the important aspects of other peoples’ cultural values in their domain. Based on this, the paper analyses the role of Sulh being an Islamic dispute settlement mechanism in the resolution of cross-cultural disputes. In doing this, it analyses burning issues of cross-cultural conflicts that have generated disputes in many countries of the world. From there, it analyses how Sulh can help resolve the world’s cross-cultural disputes. It also examines whether Muslims’ referrals of cross-cultural disputes matters to the present international dispute settlements mechanisms i.e. International Court of Justice (ICJ) and International Court of Arbitration (ICA) are in line with the Shari‛ah. The nature of the jurisdictions of ICJ and ICA are examined.